African Swine Fever Virus Transmission Cycle in Nigeria: Assessment of Domestic Pig-Soft Tick Contact through Detection of Antibodies against Ornithodoros moubata Salivary Antigen TSGP1. Issue 1 (2017) - Luka, Pam D; Mwiine, Frank N; Yakubu, Bitrus; Erume, Joseph; Pérez-Sánchez, Ricardo; Unger, Hermann
No abstract available